Rhomboid excision and Limberg flap operation for managing pilonidal sinus: our experience at Patan Hospital, Patan Academy of Health Sciences - Sanjaya Paudyal (Society of Surgeons of Nepal, 2019)
Introduction: Pilonidal sinus is a common disease. Various surgical techniques for management of sacrococcygeal pilonidal sinus have been described. Among them, the most commonly used is the rhomboid excision with the Limberg flap. With this technique of flattening the natal cleft and tension-free repair is made using a wide, well-vascularized flap. It is reported the best treatment methods, with 0-16 % of surgical area-related complications and a recurrence rate of 0-5 %. We conducted a study to evaluate the patient’s profile and outcomes of the patients of pilonidal sinus treated with rhomboid excision and Limberg flap reconstruction at our center.